Induction of polyploidy in dalbergia latifolia Roxb. using oryzalin - Riastiwi, Indira; Witjaksono,; Siregar, Ulfah Juniarti; Ratnadewi, Diah (Penerbit Universiti Kebangsaan Malaysia, 2024)
The demand for rosewood wood keeps increasing, while the availability of large-diameter rosewood trees is becoming scarce. Rosewood is classified as vulnerable by the International Union for Conservation of Nature and Natural Resources (IUCN) and listed in Appendix II of Convention of International Trade of Endangered Species (CITES). The objective of this research was to develop a method to obtain fast-growing and more vigorous rosewood seedlings for quicker harvest through polyploidy induction using oryzalin. This experiment successfully produced tetraploid rosewood through polyploidy induction from seedlings. Polyploidy induction was carried out by soaking rosewood germinated seeds for 12 and 24 h in oryzalin solutions at concentrations of 0, 3.75, 7.5, 15, 30, 45, and 120 µM. The germinated seeds were then planted in a growth medium and maintained for 18 months. Ploidy level identification of those seedlings was conducted using flow cytometry and confirmed with stomata characterizations. Two accessions of tetraploid rosewood were obtained from the treatment of 15 µM oryzalin for 12 and 24 h soaking, while seven mixoploids were obtained by treatment of 12 h at various oryzalin concentrations. Induced tetraploid seedlings had longer stomata but lower stomata density and thicker leaves than their diploid counterparts. Both induced tetraploid and mixoploid rosewood seedlings did not exhibit greater vegetative vigor than their diploids up to 18 months of age. Therefore, oryzalin induced polyploidy, mixoploid and tetraploid, but it did not produce faster growing seedlings or better habitus of rosewood compared to their diploids, at least up to 18 months.